Readiness registries: improving the effectiveness of state access and functional needs registries - Oneth, Kyle Jon (Kansas State University, 2020)
Populations with access and functional needs are a demographic group that requires specific planning and response considerations to ensure their safety during disasters. People with disabilities face greater exposure to physical hazards and are more likely to experience negative social, economic, political and psychological consequences when impacted by disasters (Wolkin, Patterson, Harris, Soler, Burrer, McGeehin and Greene, 2015). People with disabilities, therefore, are more socially vulnerable when compared to the rest of the population. This social vulnerability is further exacerbated by the higher rate of poverty and lower level of education experienced by people with disabilities. (American Psychological Association, 2019). A direct consequence of being more socially vulnerable is that people with disabilities reside in areas that are more frequently impacted by hazards correlated to lower housing costs (Hallegatte, Vogt-Schilb, Bangalore and Rozenberg, 2017). Further, on average people with disabilities have lower levels of personal preparedness than people without disabilities (Smith & Notaro, 2009). As a response to the greater level of social vulnerability to disasters and a lack of adequate local and state emergency planning, the Americans with Disabilities Act (ADA) required that those with disabilities are incorporated into emergency plans (Federal Emergency Management, 2010). Collecting basic demographic and location information about people with disabilities is a necessary first step towards more comprehensive emergency planning for people with disabilities. Statewide access and functional needs registries are a government program aimed at collecting information about people with disabilities. The data collected through these registries is intended to be utilized for emergency planning and response services. The intent of a registry varies based upon state emergency management program capabilities, and data collected can be utilized for varied planning and response interventions such as the incorporation into geographic information systems for analysis, situational awareness, priority warning, communication, decision making, evacuation, sheltering and connection of available support and resources. Multiple states have developed access and functional needs registries including Texas, New Jersey, Florida, Utah, Pennsylvania, North Dakota, Rhode Island and Delaware. These registries all have similar concepts but often vary in form and function based upon particularities of statewide needs. Despite the benefits of the information gathered from access and functional needs registries, there are some inherent difficulties in implementation that can potentially impact the overall effectiveness and success of these programs. Some issues can include advertising the program, displaying the importance of voluntarily registering, making the process accessible, ensuring security and privacy of personal information, as well as utilizing the information for the intended purposes. Due to problems similar to ones mentioned above, the access and functional needs registry program in Kansas was discontinued a few years after development, and state initiatives were redirected towards other projects. The problems faced in Kansas with the implementation of the access and functional needs registry program need to be mitigated to improve the success of the program and ensure maximum effectiveness. Through an analysis of the Texas, Florida and New Jersey access and functional needs registries, the report gathers insight into their utilization, challenges faced and perspectives, that will help identify potential variables that could impact the program’s effectiveness. Once identified, these inherent issues with access and functional needs registries can be mitigated so the effectiveness, success and benefits provided by these registries can be utilized for the integration into emergency plans and to help create an environment for an inclusive planning process involving some of the most vulnerable populations in the state of Kansas.
Keywords: Disabilities